2011
DOI: 10.1158/1078-0432.ccr-10-2729
|View full text |Cite
|
Sign up to set email alerts
|

KLF4-Mediated Negative Regulation of IFITM3 Expression Plays a Critical Role in Colon Cancer Pathogenesis

Abstract: Purpose IFITM3, an interferon-inducible gene, is overexpressed in human colorectal cancer. In this study, we sought to determine the clinical significance and underlying mechanisms of its dysregulated expression in human colon tumor specimens and murine models of this disease. Experimental Design IFITM3 expression in a tissue microarray of tumor and matched normal colon tissue specimens and lymph node metastasis specimens obtained from 203 patients with colon cancer was measured immunohistochemically. Resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(109 citation statements)
references
References 33 publications
3
106
0
Order By: Relevance
“…IHC staining was performed as described previously [17, 18]. KLF7 anti-human rabbit antibody was used at a dilution of 1: 100 (ab197690, Abcam); PBS was used as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…IHC staining was performed as described previously [17, 18]. KLF7 anti-human rabbit antibody was used at a dilution of 1: 100 (ab197690, Abcam); PBS was used as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…Construction of the TMA and IHC staining were performed as described previously (9,10). Gas1 and FOXM1 anti-human rabbit polyclonal antibodies were used at a dilution of 1:100 (AP11869a; Abgent) and 1:50 (sr-500; Santa Cruz Biotechnology), respectively; PBS was used alternately as negative control.…”
Section: Construction Of the Tma And Ihc Stainingmentioning
confidence: 99%
“…Current studies in carcinogen-esis have revealed that KLF4 can function as both tumor promoter and tumor suppressor depending on tissue type and cellular context [241]. The oncogenic effect of KLF4 has been reported in breast and squamous cell carcinoma [243][244][245][246][247], while its tumor suppression role was reported in various types of cancers such as colon cancer [248,249]. It was demonstrated that KLF4 is a fast turnover protein, whose turnover-half life is governed by the ubiquitin-proteasome system [250,251].…”
Section: Crosstalk With Tgf-β Signalingmentioning
confidence: 99%